(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to find out (the effect of teaching using the (ASSURE) model on the achievement of fifth-grade students in science item), by checking the following two null hypotheses: - There is no statistically significant difference at the level (0.05) between the average scores of the experimental group who will study the description of the model (ASSURE) and the average scores of the control group who will study according to the traditional method in the achievement test. The current research represents all fifth grade primary school students in schools affiliated to the Directorate of Education of Baghdad Governorate Rusafa First for the academic year (2021-2022), (Rand School) was chosen randomly to represent the current research sample of divided into three divisions (A, B, C). Two divisions (A, B) were chosen by simple random assignment. The total number was (60) female students for the fifth grade of primary school, by (30) female students for group (A) to represent the control group that studies according to the usual method, division (B) (30) students to represent the experimental group that is studying according to the Assure model.The experimental design with two groups (experimental and control) was adopted, one of which controlled the other partially with the post-test of achievement and skills of collecting and organizing information. The content of the current research was determined in the first and second units of the science book for the fifth grade of primary school, as it was analyzed into )149( behavioral objectives in light of the six levels of Bloom’s classification of the cognitive domain (remember, understanding, application, analysis, installation, evaluation).(24) daily teaching plans were prepared for the experimental group and the same for the control group according to the traditional method. prepared the two research tools with the first test, an achievement test consisting of (28) objective paragraphs of a multiple-choice type with four alternatives. The second is a test of information gathering and organization skills, which includes (25) items, and its validity and reliability were verified, as it reached (0.85) and (0.866) for the collection items and the skills of collecting and organizing information, respectively, as well as calculating the psychometric properties of the two tools’ items.The researcher applied the experiment in the first semester of the academic year (2021-2022) and lasted (7) weeks, with (4) lessons per week for each group.Using the t-test equation for two independent samples, the results showed a significant difference in the achievement variable and the skills of collecting and organizing information in favor of the experimental group who studied according to the (ASSURE) model over its peers in the control group who studied according to the traditional method.In light of the results, the researcher recommended several recommendations, the most important of which is the necessity of using the (ASSURE) model and working on how to use it in explaining science lessons to develop students’ abilities and to raise the achievement and scientific